Editorial: Neuromuscular training and adaptations in youth athletes - Granacher, U.; Puta, C.; Gabriel, H. H.; Behm, D. G.; Arampatzis, A. (Frontiers in Physiology, 2018)
The aims of our Research Topic entitled "Neuromuscular Training and Adaptations in Youth Athletes" were to provide in-depth knowledge in the form of original work, review articles, and meta-analyses on the effects of NT on muscular fitness, athletic performance, and injury prevention in young athletes during the different stages of LTAD.